Pancasila Dan Keluarga: Upaya Membangun Generasi Unggul Berwawasan Kebangsaan Menuju Indonesia Emas - Kusuma Putri; Gede Agus Siswadi (University of Muhammadiyah Malang, 2026)
The family plays a fundamental role in shaping generations by cultivating and transmitting the values of Pancasila, which serves as the identity, ideology, and philosophical foundation of the Indonesian state. These values provide a framework for developing national awareness among younger generations. This study aims to examine the relationship between the family and Pancasila in fostering a distinguished generation with strong national insight toward the realization of Indonesia Emas. A distinguished generation is defined as one that possesses both intellectual competence and strong moral character, enabling it to contribute meaningfully to national development across various sectors. This research employs a descriptive qualitative method, utilizing a literature review and philosophical analysis. Family-related data are analyzed through the perspective of Pancasila values, particularly those that strengthen character formation and national awareness. The findings reveal that both the family and Pancasila hold a central role in developing a generation that is not only intellectually capable but also ethically grounded and nationally conscious. Such a generation functions as a driving force for progressive and contributive national development. Furthermore, Pancasila provides a core value system that supports the formation of national insight, guiding individuals toward becoming responsible and capable citizens. The study highlights the importance of reinforcing the role of the family as the primary environment for value internalization. It also underscores the need for stronger synergy between the family and the state to build a shared commitment toward achieving Indonesia Emas. This vision emphasizes not only progress but also the prioritization of humanistic values, beginning within the family sphere.